La devoción a Santo Domingo en Soriano en la iglesia del Real Convento de Predicadores de Zaragoza - Esponera Cerdán, Alfonso (Archivo Dominicano, 2023)
The devotion of Saint Dominic in Soriano had certain characteristics that make it quite peculiar. From the 17th century it became a common in the temples of many convents of Dominican friars, especially in Italy, Spain and Latin America. This work presents this devotion in relation to the poorly studied Royal Convent of Preachers in the Spanish Zaragoza until the first half of the 18th century, based on the unpublished writings of the Dominican friar Jose Lamana.